Comparison of Clinical Features Between Primary and Secondary Breast Diffuse Large B Cell Lymphoma: A Yokohama Cooperative Study Group for Hematology Multicenter Retrospective Study - Takahashi, Hiroyuki (Indian J Hematol Blood Transfus, 2020)
We performed a retrospective analysis of DLBCL with breast involvement to compare the prognosis of primary breast lymphoma (PBL) to secondary breast lymphoma (SBL; especially in limited stage cases). We retrospectively reviewed records of 25 diffuse large B-cell lymphoma (DLBCL) patients with breast involvement who received chemotherapy between January 2000 and August 2012. We compared clinical features and prognosis among patients with PBL (n = 11), limited stage SBL (LSBL; n = 6), and advanced stage SBL (ASBL, n = 8). The PBL group had significantly lesser patients with breast tumours (BTs) > 5 cm than the SBL group (P = 0.02). After a median follow-up of 71.3 months, we observed significantly better 5-year overall survival (OS) in the PBL group (90.0%) than in the LSBL (33.3%, P = 0.01) group, but not for progression-free survival (PFS). Patients with BT > 5 cm had worse OS (P = 0.01) and PFS (P = 0.04) than those with BT ≤ 5 cm. PBL had a better prognosis than SBL among limited stage DLBCL.